PENILAIAN TINGKAT KESEHATAN BANK MELALUI ANALISA METODE CAMEL DAN PENGUNGKAPANNYA DALAM LAPORAN KEUANGAN PADA PT. BANK EKONOMI RAHARJA TBK CABANG PONTIANAK - B51110022, MASITA YUDA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This study aims to determine the health level of PT. Bank Ekonomi Raharja Tbk Branch Pontianak using CAMEL method over the period 2011-2013. Whether in the period included in the category of healthy, quite healthy, less healthy or unhealthy.CAMEL has five aspects, namely capital using the ratio of CAR (Capital Adequacy Ratio), aspects of asset quality using the ratio KAP (Assets Quality) and PPAP (Allowance for Earning Assets), management uses calculations general management and risk management, aspects profitability using ROA (Return on Assets) and BOPO (Operating Expenses to Operating Income), and the liquidity aspect using ratio CR (Cash ratio) and LDR (Loan to Deposit Ratio).This research is quantitative. The analytical tool used in this research is by using the CAMEL based on the Decree of Directors of Bank Indonesia Number 30/12 / KEP / DIR dated 30 April 1997 concerning Procedures for Rating Bank.As a benchmark for determining the soundness of a bank after conducting an assessment of each of the variables is to determine the results of the research will then be classified into health predicate Bank. The type of data used is primary data obtained through interviews and secondary data, the financial statements of the balance sheet and income statement at. Bank Ekonomi Raharja Tbk Branch Pontianak 2011-2013 .Based on the research that has been conducted at PT. Bank Ekonomi Raharja Tbk Branch Pontianak 2011-2013 period, PT. Bank Ekonomi Raharja Tbk Branch Pontianak awarded HEALTHY. Because CAMEL credit score of more than 81 ( the minimum limit of healthy ) is 89.77 in 2011, 91.70 in 2012 and 97.73 in 2013.Keywords : Health Bank, Ratio of CAMEL